Syria's Passage to Conflict: The End of the "Developmental Rentier Fix" and the Consolidation of New Elite Rule. (December 2016) - Azmeh, Shamel
Syria's descent into conflict is receiving growing scholarly attention. On their own, the sectarian and geopolitical interpretations of the Syrian conflict provide us with little understanding of the roots of the conflict. Recent studies have started to unpack the political economic and socioeconomics aspects of the conflict, highlighting issues such as the economic reforms in the 2000s, rising inequality, and climate change. This article aims to contribute to this growing literature by placing these issues in a broader analysis of Syria's political and economic institutions. It argues that the movement of 2011 should be seen as an unorganized protest movement driven by the consolidation and institutionalization of multisectarian elite rule through the economic reform process that started in the 2000s, following the expiration of the "developmental rentier fix" that had ensured authoritarian stability in Syria in earlier decades.